2014
DOI: 10.1074/jbc.m114.569632
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Lymphoma-2 (BCL-2) Homology Domain 3 (BH3) Mimetics Demonstrate Differential Activities Dependent upon the Functional Repertoire of Pro- and Anti-apoptotic BCL-2 Family Proteins

Abstract: Background: BH3 mimetics are promising chemotherapeutics, but their full mechanisms of action are underexplored. Results: BAX, BID, and BIM directly influence BH3 mimetics to pharmacologically inhibit anti-apoptotic BCL-2 proteins. Conclusion: BH3 mimetics display differential activities that are dependent upon both anti-and proapoptotic BCL-2 members function. Significance: Understanding how BH3 mimetics function within the BCL-2 family repertoire will improve the utility of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…However, levels of this protein do not correlate with in vivo response of pediatric ALL xenografts [82 ]. Using liposomes and recombinant proteins, Renault et al have found that not only anti-apoptotic proteins but also proapoptotic members of the family contribute to determining the response to specific BH3-mimetics [83]. Clearly, these results indicate that predicting the sensitivity of BH3-mimetics will probably require more complex systems that include several players of the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 95%
“…However, levels of this protein do not correlate with in vivo response of pediatric ALL xenografts [82 ]. Using liposomes and recombinant proteins, Renault et al have found that not only anti-apoptotic proteins but also proapoptotic members of the family contribute to determining the response to specific BH3-mimetics [83]. Clearly, these results indicate that predicting the sensitivity of BH3-mimetics will probably require more complex systems that include several players of the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 95%
“…18 Therefore, dual-target inhibitor, such as TW-37, has the specific potential application. 19 Both CDDP and 5-Fu decrease protein level of Bcl-2 and Mcl-1 in NPC cells. This result is comparable with several kinds of cancer.…”
Section: Discussionmentioning
confidence: 92%
“…The second model suggests that mitochondrial apoptogenic factors can be released through the pores in the OMM formed by the pro-apoptotic Bcl-2 family members that do not affect m . Key members of the anti-apoptotic (Bcl-2, Bcl-x L , and Bcl-w) and proapoptotic (Bax, Bak, Bad, Bim and Bid) Bcl-2 family of proteins are major players in the OMM permeabilisation and apoptotic susceptibility in this model of cytosolic release of apoptogenic mediators [59].…”
Section: Caspase-dependent and -Independent Programmed Cell Deathmentioning
confidence: 99%